Nutritional Content Dynamics and Correlation of Bacterial Communities and Metabolites in Fermented Pickled Radishes Supplemented With Wheat Bran - Li, Xiaoqiong; Liu, Daqun (Frontiers in Nutrition, 2022)
Wheat bran supplementation in cereal food processing improves the nutritional value and quality of the final products. However, whether wheat bran has the potential as a biofortifier to enhance nutritional and flavor of fermented vegetables remains unknown. The study aimed to evaluate the potential of wheat bran supplementation for nutrition and flavor fortification during radish fermentation, and to explore the role of microorganisms in nutritional and flavors development. Using high-throughput sequencing coupled with high-performance liquid chromatography and headspace solid-phase microextraction-gas chromatography-mass spectrometry, the microbial community profiles and nutritional and flavor changes of wheat bran-treated samples were analyzed and compared with control samples. Correlation analysis between bacteria taxa with metabolites were also performed. The results showed that wheat bran treatment increased the content of most free amino acids (FAAs), α-linolenate, thiamine, and riboflavin in the samples (p < 0.05). In addition, the increased consumption of reducing sugar and glutamate in the wheat bran-treated samples was due to the production of secondary metabolites such as lactic acid, ethanol, acetic acid, and GABA (p < 0.05). Moreover, compared with control samples, the flavor of the wheat bran-treated pickled radish was preferable. Wheat bran increased the amount of alcohol, ester, acid, and ketones compounds but reduced the number of sulfides, which increased the aroma but decreased the pungent flavor. Additionally, the correlation analysis suggested that Lactobacillus, the most dominant genus, was boosted by wheat bran and was positively associated with most of FAAs, GABA, and lactate, while negatively associated with most sulfides. Therefore, compared with the control, wheat bran treatment could improve the nutritional values and sensorial properties of radish pickles. New areas of research should explore the co-fermentation of other vegetables with wheat bran, and the potential of this processing technique to provide consumers with products of high nutritional quality.